An efficient certificateless signature scheme - Yap, Wun She; Heng, Swee Huay; Goi, Bok Min (Springer Berlin Heidelberg, 2006)
Certificateless public key cryptography (CLPKC) is a paradigm to solve the inherent key escrow problem suffered by identity-based cryptography (IBC). While certificateless signature is one of the most important security primitives in CLPKC, there are relatively few proposed schemes in the literature. In this paper, we manage to construct an efficient certificateless signature scheme based on the intractability of the computational Diffie-Hellman problem. By using a shorter public key, two pairing computations can be saved in the verification algorithm. Besides, no pairing computation is needed in the signing algorithm. The proposed scheme is existential unforgeable in the random oracle model. We also present an extended construction whose trust level is the same as that of a traditional signature scheme.